Refugee children's access to critical healthcare services in South Africa - Kaponda, Tatenda (Department of Public Law, 2024)
Access to socio-economic rights in a host country by refugees is important in ensuring successful integration. Despite rights being afforded to refugees in international law in theory, their practical realisation is often fraught with difficulties. This study sought to focus on the most vulnerable of the refugee population, children, and their access to critical healthcare services in South Africa. It sought to analyse refugee children's access to critical healthcare services from a human rights approach focusing on the key principles of non-discrimination and human dignity. The study found that although refugee children's access to critical healthcare services is widely provided for in theory, several barriers exist to the realisation of this right. The study concludes by making recommendations on how various parties can contribute to improving refugee children's access to critical healthcare services